Study Of Important Psychosocial Factors in Institutionalized Blinds - Kumbhar, Uddhav T.; Dehmubed, Armaity (National Journal of Community Medicine, 2011)
Background: Blindness probably is the most feared infirmity of mankind. The blind individuals were considered useless for the centuries till recent development in culture and civilization. Present study was conducted with the aim to study important psychosocial aspects of blinds undergoing formal vocational training in institutes. Objective: to identify candidates’ psychosocial profile using Self Reporting Questionnaire (S.R.Q.). Materials and Methods: it was a cross sectional study conducted in two vocational training institutes for blinds (one for males and other for females) in Mumbai. The individuals were subjected to pre tested S.R.Q. and the individuals found positive with this tool and double the number of matched S.R.Q. negative controls from the institute were subjected to psychiatric examination done by qualified psychiatrist. Analysis: analysis was done using fisher’s exact test and chi square test results: 15 (7.18%) blinds were found S.R.Q. positive indicating they either have or prone to have psychiatric morbidity. Conclusion: Psychological rehabilitation of the blinds should be considered before planning the vocational training of blinds.